The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/ejh.13494
|View full text |Cite
|
Sign up to set email alerts
|

Life expectancy and cause of death in individuals with haemophilia A and B in Norway, 1986‐2018

Abstract: Objectives: Evaluate trends over time in age-and cause of death in males with haemophilia (PWH) in Norway compared with the general male population and investigate its correlates with improvements in haemophilia treatment. Methods: Data about age and cause of death in the period of 1986-2018, from two independent, high-quality national registries: the Norwegian Cause of Death Registry (NCoDR) and the patient registry at Centre for Rare Disorders (CRD), Oslo University Hospital. Results: Life expectancy increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Thirty studies describing causes of death in the overall PWH population were used to examine proportionate mortality 1–2,7–12,14,17–18,25–43 . Causes of mortality were extracted for a total of 7703 deaths.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty studies describing causes of death in the overall PWH population were used to examine proportionate mortality 1–2,7–12,14,17–18,25–43 . Causes of mortality were extracted for a total of 7703 deaths.…”
Section: Resultsmentioning
confidence: 99%
“…Altogether 47 studies reported causes of death. Of them, 30 non‐overlapping studies 1–2,7–12,14,17–18,25–43 reported proportionate mortality in the overall PWH population and are presented in Tables 3–4. Results from 17 studies that reported causes of death in subpopulations of PWH or are overlapping with other studies are presented in the supplementary appendix 13,15,19–20,44–58 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 19 This is also noted in an analysis of life expectancy and cause of death in individuals with hemophilia A and B in Norway from 1986-2018, which showed that the persons with severe hemophilia died at a mean age of 53.4±21.7 compared to 71.5±19.6 for mild and moderate hemophilia. 20 …”
Section: Discussionmentioning
confidence: 99%
“…Major advances in therapy and treatment strategies have been reflected in an increased life expectancy and improved quality of life for people with haemophilia (PWH). [1][2][3] However, as PWH of all severities without inhibitors now have longer life expectancy, an increase in the incidence of cardiovascular diseases (CVDs), cancer, and other comorbidities is to be expected, 4,5 especially as PWH are equally or even more prone to CV risk factors such as obesity, hypertension, and diabetes than the general population. 6 - 11 For example, a retrospective study of PWHA/B aged ≥40 years who attended the Gulf States Hemophilia and Thrombophilia Center (GSHTC) reported that 78% of the study population had at least one CV risk factor including hypertension (46%), overweight/obesity (65%), high cholesterol (16%), or/and diabetes mellitus (14%).…”
Section: Introductionmentioning
confidence: 99%